Group Cohesion and Radical Narratives on Instagram: A Symbolic Convergence Analysis of @muslimahnewwsid - Siti Isnaini; Shafira Putri Ziyan Abidin; Fita Lia Nuriyah Agustin (Sekretariat Badan Moderasi Beragama dan Pengembangan Sumber Daya Manusia (BMBPSDM) Kementerian Agama RI, 2026)
The increasing use of social media has enabled the rapid dissemination of ideological narratives and facilitated the formation of online communities based on shared beliefs. One account that has attracted public attention is @muslimahnewsid, which is often associated with narratives rejecting democracy, promoting the caliphate, and criticizing religious moderation. However, limited research has examined how these narratives contribute to the formation of group cohesion among followers. This study aims to analyze how fantasy themes, fantasy chains, and rhetorical visions are constructed in the Instagram content of @muslimahnewsid using Symbolic Convergence Theory (SCT). This study employed a qualitative approach with content analysis. Data consisted of three Instagram video posts selected from ten purposively sampled posts uploaded between January 2024 and March 2025. The analysis focused on captions, visual elements, and audience comments. To strengthen the findings, in-depth interviews were conducted with expert informants. The findings show that the account constructs fantasy themes centered on leadership crisis, the delegitimization of democracy, and the idealization of the caliphate. These narratives are reinforced through audience interactions, forming fantasy chains that ultimately generate a rhetorical vision portraying Islamic governance as the preferred alternative. The study concludes that symbolic communication plays a significant role in fostering ideological cohesion and collective identity within digital communities.